2023
DOI: 10.1002/ajh.26909
|View full text |Cite
|
Sign up to set email alerts
|

Tissue iron distribution in patients with anemia of inflammation: Results of a pilot study

Abstract: Anemia of inflammation (AI) is frequently present in subjects with inflammatory disorders, primarily caused by inflammation-driven iron retention in macrophages. So far, only limited data on qualitative and quantitative estimates of tissue iron retention in AI patients exist. We performed a prospective cohort study analyzing splenic, hepatic, pancreatic, and cardiac iron content with MRI-based R2*-relaxometry in AI patients, including subjects with concomitant true iron deficiency (AI+IDA) hospitalized between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(136 reference statements)
0
0
0
Order By: Relevance
“…MRI methods, used to assess iron status and more likely to be available in high-resource settings, have capabilities superior to common serum-based assays in detecting iron content in tissues. As discussed above, a study assessing iron retention in patients with anemia of inflammation, confirmed findings from animal models of iron retention in macrophages [3]. These findings point towards improved biomarker thresholds to assess iron deficiency in patients with inflammatory conditions.…”
Section: Non-serum Based Assessment Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…MRI methods, used to assess iron status and more likely to be available in high-resource settings, have capabilities superior to common serum-based assays in detecting iron content in tissues. As discussed above, a study assessing iron retention in patients with anemia of inflammation, confirmed findings from animal models of iron retention in macrophages [3]. These findings point towards improved biomarker thresholds to assess iron deficiency in patients with inflammatory conditions.…”
Section: Non-serum Based Assessment Methodssupporting
confidence: 68%
“…Ferritin, commonly used to assess iron stores, is an acute-phase protein that increases in response to inflammation making it less useful as a biomarker. Distinguishing anemia of inflammation from true iron deficiency anemia remains a gap in knowledge, and MRI offers the potential to assess iron content in multiple tissues including in the liver, pancreas and heart [3]. This approach was noted as having the potential to better identify and treat people with anemia of inflammation, typically characterized with lower serum iron and transferrin saturation and higher ferritin levels compared to people with anemia of inflammation and iron deficiency anemia.…”
Section: Inflammationmentioning
confidence: 99%
“…Neopterin, reflecting activation of monocytes and macrophages, and also hepcidin levels were correlated with spleen R2* values, while there was only a trend for correlation with liver R2* values, suggesting that inflammation-related iron restriction might primarily occur in the spleen. This is supported by animal models that demonstrated that macrophages withholding iron primarily accumulate in the spleen under inflammatory conditions [ 54 , 55 ], which could also be confirmed by a recent MRI investigation showing that patients with inflammatory anemia primarily accumulate iron in the spleen [ 56 ].…”
Section: Discussionmentioning
confidence: 67%
“…It can be speculated that intravenous iron supplementation might be suitable for patients with empty iron stores, while it will not be effective in patients with functional ID due to already existing inflammation and hepcidin‐driven iron retention in macrophages mainly of the spleen. 31 In fact, iron supplementation to individuals with inflammation can further promote macrophage iron accumulation and tissue iron retention with eventual radical formation and cellular injury, while iron is insufficiently available for erythropoiesis. 32 , 33 , 34 In contrast, minute amounts of iron supplemented to patients with inflammation along with empty iron stores (combined ID) is accessible for erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%